Digital Literacy Campaign to Improve the Community's Economy - Lyandra Arianti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The growing digital era has had a significant impact on various aspects of life, including the economy. Digital understanding and proficiency is key to helping society deal with this change. Therefore, we held a community service program entitled